Study of the Condition of Mackerel Scad Stocks (Decapterus sp) in Ternate Island Waters - Tangke, Umar; Talib, Ahmad (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
Mackerl scad, is an economically important small pelagic fish species in the waters of Ternate Island which is exploited by fishermen with various types of active fishing gear such as purse seine, bagan and gill net. The use of fishing gear that is less selective with fishing activities throughout the year and not equipped with utilization regulations, is expected to cause pressure on skipjack stocks in the waters of Ternate Island. . This research is a type of empirical research carried out using the experimental fishing method, in which the researcher participates in fishing activities for 120 trips and samples of the fish caught are taken for the measurement process in the Lab. Processing of Fishery Products for 5 months, from October 2022 to March 2023. The results showed that the condition of the flyfish population parameter in Ternate Island waters was relatively stable with a maximum length value of 33.49 cm, a growth coefficient of 0.99 per month, fishing mortality 0.42, natural mortality 1.71 , the exploitation rate is 0.2 and the SPR is 42% and the recruitment value is Y/R 1.9% and B/R 56.8%. Where from these results indicate the need for an increase in fishing effort until the exploitation value reaches 0.4 for optimal and sustainable management.